Agroecological mapping of livestock feed resources for sustain productivity and climate resilience in Benin (West Africa) - Marthe Montcho; Alassan S. Assani; Jean de Dieu Ainamon; André B. Aboh; Pascal A. Olounladé; Brice Sinsin (Discover Sustainability)
Abstract  Feed availability and accessibility are two of the main challenges for Benin livestock systems, which are currently subject to environmental stress and changing climatic conditions. The aim of this study was to assess the main fodder resources used by livestock in Benin by estimating fodder supply and demand for livestock in Benin's agroecological zones (AEZs) and establishing a fodder balance. A total of 314 agrofarmers were surveyed using simple random sampling. Data were collected through discussions with agropastoralists, structured questionnaires, secondary data and observations. The survey in the eight AEZs of Benin revealed that maize residues are the main crop residues used in livestock feed (53.14%), followed by sorghum residues (8.41%), millet (5.91%), soya (8.1%) and rice (5). It also found that natural grazing areas are the main fodder resources used in Benin, with a dry matter contribution of 74% compared with 26% for crop residues. The study of the availability of fodder resources revealed a positive fodder balance for dry matter (DM) in each agroecological zone, but a negative balance in all AEZs for metabolizable energy (ME) and digestible crude protein (DCP). Thus, with an average annual availability of almost 3.15 million tons of DM across all Benin AEZs, zones 2, 3 and 5 had the highest DM availability rates, while AEZs 1, 7 and 8 had the lowest DM availability. To alleviate this problem of food shortages for livestock, we suggest interventions to improve the productivity of grazing areas; The introduction of fodder crops with the emphasis on legumes and efficient use of available fodder resources, such as the treatment of livestock feed (treatment of poor fodder with urea is one example).